Arginase-1 targeting peptide vaccine in patients with metastatic solid tumors – A phase I trial - Lorentzen, Cathrine Lund; Martinenaite, Evelina; Kjeldsen, Julie Westerlin; Holmstroem, Rikke Boedker; Mørk, Sofie Kirial; Pedersen, Ayako Wakatsuki; Ehrnrooth, Eva; Andersen, Mads Hald; Svane, Inge Marie (Frontiers in Immunology, 2022)
Background Arginase-1-producing cells inhibit T cell-mediated anti-tumor responses by reducing L-arginine levels in the tumor microenvironment. T cell-facilitated elimination of arginase-1-expressing cells could potentially restore L-arginine levels and improve anti-tumor responses. The activation of arginase-1-specific T cells may convert the immunosuppressive tumor microenvironment and induce or strengthen local Th1 inflammation. In the current clinical study, we examined the safety and immunogenicity of arginase-1-based peptide vaccination. Methods In this clinical phase I trial, ten patients with treatment-refractory progressive solid tumors were treated. The patients received an arginase-1 peptide vaccine comprising three 20-mer peptides from the ARG1 immunological “hot spot” region in combination with the adjuvant Montanide ISA-51. The vaccines were administered subcutaneously every third week (maximum 16 vaccines). The primary endpoint was to evaluate safety assessed by Common Terminology Criteria for Adverse Events 4.0 and laboratory monitoring. Vaccine-specific immune responses were evaluated using enzyme-linked immune absorbent spot assays and intracellular cytokine staining on peripheral blood mononuclear cells. Clinical responses were evaluated using Response Evaluation Criteria in Solid Tumors 1.1. Results The vaccination was feasible, and no vaccine-related grade 3–4 adverse events were registered. Nine (90%) of ten patients exhibited peptide-specific immune responses in peripheral blood mononuclear cells. Six (86%) of the seven evaluable patients developed a reactive T cell response against at least one of the ARG1 peptides during treatment. A phenotypic classification revealed that arginase-1 vaccine-specific T cells were both CD4+ T cells and CD8+ T cells. Two (20%) of ten patients obtained stable disease for respectively four- and seven months on vaccination treatment. Conclusion The peptide vaccine against arginase-1 was safe. Nine (90%) of ten patients had measurable peptide-specific responses in the periphery blood, and two (20%) of ten patients attained stable disease on protocol treatment. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT03689192, identifier NCT03689192.